2022
DOI: 10.1007/s00580-021-03311-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and COVID-19: challenges and opportunities

Abstract: Coronavirus disease 2019 or COVID-19, starting from Wuhan, China, in December 2019, is a pandemic situation affecting millions worldwide and has exerted a huge burden on healthcare infrastructure. Therefore, there is an urgent need to understand the molecular mechanisms underlying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and design novel effective therapeutic strategies for combating this pandemic. In this regard, special attention has been paid to the exosomes. These nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…As single-membrane and secreted organelles (30 to 200 nm in diameter), exosomes have the same topology as host cells, and the contents or functions of exosomes are affected by the cellular environment [ 16 , 17 , 18 ]. Exosomes derived from hypoxia-preconditioned BMSCs demonstrated up-regulated expression of HIF-1α, which could be utilized to alleviate cisplatin-induced ototoxicity with increased auditory sensitivity, alleviated hair cell loss, and diminished oxidative stress when compared with exosomes derived from BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…As single-membrane and secreted organelles (30 to 200 nm in diameter), exosomes have the same topology as host cells, and the contents or functions of exosomes are affected by the cellular environment [ 16 , 17 , 18 ]. Exosomes derived from hypoxia-preconditioned BMSCs demonstrated up-regulated expression of HIF-1α, which could be utilized to alleviate cisplatin-induced ototoxicity with increased auditory sensitivity, alleviated hair cell loss, and diminished oxidative stress when compared with exosomes derived from BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although Exos enhance virus transmission, it can also enhance the expression of CD9 and ACE2 in uninfected cells, which facilitate viral docking and recipient cell susceptibility. 17 , 53 , 54 We believe that modifying VSTs‐derived Exos to target ACE2 mRNA can play a role in the downregulation of ACE2 expression. VSTs‐Exos loaded with miRNAs targeting ACE2 mRNA will directly inhibit the expression of ACE2 leading to prevent viral entry.…”
Section: Potential Efficacy Of Exos Derived From Immune Cellsmentioning
confidence: 98%
“…This could imply that immune mediators are involved in viral genome mutations by inducing specific intracellular pathways, as recently reported in cancer that mutations in various genes, such as C2, CD163L1 or FCR2A, have been linked to increased or decreased immune cell infiltration, depending on the specific domain altered. 16 On the other hand, some studies revealed that extracellular vesicles or exosomes (Exos) released from virus‐infected cells essentially contribute to promoting viral transmission and replication, 17 as presented in Figure 2 . Exos released by virus‐infected immune cells could enhance the exhaustion of T‐cell subsets.…”
Section: Introductionmentioning
confidence: 99%
“…The binding efficacy of the exosome to the spike protein is explained in Table 2 . This significantly increases the probability of miRNA transfer between the virus and the vesicles and is the suitable EVS [ 29 ]. Estimating the number of exosomes in a given source is necessary to find the ideal sources.…”
Section: Source Exosomes and Selective Protein Binding Efficacy In Co...mentioning
confidence: 99%